Neurodevelopmental Outcome of Treatment of Symptomatic CMV Infection with Ganciclovir (Bangladesh Journal of Child Health, 2012)
Rationale: Cytomegalovirus (CMV) infection is a common cause for neurodisability among poor populations in developing countries, including Bangladesh. Some studies have shown that ganciclovir therapy is effective in reducing neurodevelopmental morbidity; while others remain equivocal.Objective : The objective of this study was to evaluate neurodevelopmental outcome of children with symptomatic CMV treated with ganciclovir compared to matched control.Methods: Out of 218 children seropositive for CMV admitted into the neurology ward between 2003-2006, 91 were treated with intravenous ganciclovir for 2-3 weeks; of whom 43 came for follow-up at an interval of 3 months to 1 year. At each visit neurodevelopmental status was recorded for cognition, vision and hearing. 41 untreated age-matched cases with follow-up records were retrospectively enrolled as control.Results: Among treated children compared to untreated controls, there was significant improvement in hearing (58% vs. 27%; p value=.012). Improvement remained consistent, without statistical significance, for vision (53% vs. 39%; p value=.071)) and cognition (51% vs. 54%; p value=.344).Conclusion: Ganciclovir treatment improved neurodevelopmental outcomes of very young children with symptomatic CMV infection. In a country where limited resources are available for children with disability, early recognition and treatment of CMV infection is recommended.DOI: http://dx.doi.org/10.3329/bjch.v35i3.10498  Bangladesh J Child Health 2011; Vol 35 (3): 97-101